Cavernous Carotid Pseudoaneurysm Following Transsphenoidal Surgery. Issue 3 (13th January 2012) - Fu, Michael; Patel, Toral; Baehring, Joachim M.; Bulsara, Ketan R.
ABSTRACT: Pseudoaneurysm of the internal carotid artery (ICA) as a result of injury during transsphenoidal surgery is a rare but serious complication. We present a review of this subject, identifying 22 such cases in the literature, and contribute an unusual case of our own. Among our cohort, 23% of patients had no evidence of vascular injury or hemorrhage during the initial transsphenoidal operation, and presented at an average of 83 days after surgery. The average time to diagnosis for patients with intraoperative bleeding was 64 days after surgery. Epistaxis was the most common initial presenting symptom, seen in 41% of patients, and traditional angiography was employed in every case to make the diagnosis of pseudoaneurysm. Though complete occlusion of the ICA was ultimately required in 41% of patients, the remainder were treated with a variety of modalities. While intraoperative hemorrhage is certainly the most predictive indicator of iatrogenic vascular damage, in its absence, other signs such as postoperative bruits may be predictive of pseudoaneurysm formation as well. The continued accumulation of these unique cases will hopefully provide definitive recommendations on the early recognition and treatment of this serious condition, especially regarding the emerging role of endovascular therapy in its management.